Time scales and the asymptotics for the solutionsof discrete adiabatic oscillators - P. N. Nesterov (Моделирование и анализ информационных систем, 2011)
We develop a method of averaging for the study of linear systems of dynamic equations on time scales. We use the obtained results to construct the asymptotics for the solutions of some equations of discrete adiabatic oscillators.